Strategies to improve energy efficiency in sewage treatment plants - Au M.T.; Pasupuleti J.; Chua K.H. (Institute of Physics Publishing, 2023)
This paper discusses on strategies to improve energy efficiency in Sewage Treatment Plant (STP). Four types of STP; conventional activated sludge, extended aeration, oxidation ditch, and sequence batch reactor are presented and strategized to reduce energy consumption based on their influent flow. Strategies to reduce energy consumption include the use of energy saving devices, energy efficient motors, automation/control and modification of processes. It is envisaged that 20-30% of energy could be saved from these initiatives. Published under licence by IOP Publishing Ltd.